1989
DOI: 10.1093/infdis/160.4.577
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Concurrent Human Immunodeficiency Virus Infection on Chronic Hepatitis B: A Study of 150 Homosexual Men

Abstract: To determine the influence of concurrent human immunodeficiency virus (HIV) infection on chronic hepatitis B virus (HBV) infection, 150 male homosexual chronic hepatitis B surface antigen (HBsAg) carriers were studied. Of these, 82 subjects (55%) tested positive for antibodies to HIV. They were more likely to express hepatitis B "e" antigen (HBeAg) (P less than .001) and HBV-DNA (P less than .0005) in serum than were HIV-seronegative individuals. However, the degree of immune suppression did not influence HBeA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
2
5

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(79 citation statements)
references
References 19 publications
3
68
2
5
Order By: Relevance
“…[22][23][24][25][26] In addition, immunosuppressed persons are more likely to develop chronic HBV infection after acute infection. 27,28 …”
Section: Epidemiology Of Hepatitis Bmentioning
confidence: 99%
See 2 more Smart Citations
“…[22][23][24][25][26] In addition, immunosuppressed persons are more likely to develop chronic HBV infection after acute infection. 27,28 …”
Section: Epidemiology Of Hepatitis Bmentioning
confidence: 99%
“…[29][30][31][32][33]43 The rate of clearance of HBeAg is much lower in Asian children (most of whom have normal ALT levels) 34,35 and in immunocompromised subjects. 28,44 The largest prospective follow-up study conducted in Alaska of 1,536 carrier children and adults, followed for 12 years, showed that spontaneous HBeAg clearance occurred in 45% of carriers in 5 years and in 80% after 10 years. 43 Similarly, 3-and 5-year HBeAg clearance rates of 50% and 70% were reported in untreated children with elevated ALT levels from Taiwan and Italy.…”
Section: Terminology and Natural History Of Chronic Hbv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high prevalence of HBeAg in both groups was found; coinfected patients had a significantly higher value than the mono-infected controls. Higher HBeAg prevalence in HIV/HBV co-infected patients than in HBV monoinfected subjects has also been observed in both developed nations and sub-Saharan Africa [4,18,[21][22][23].…”
Section: Discussionmentioning
confidence: 83%
“…First, both have a stage of reverse transcription in their replication cycle. Second, destruction of HBV infected hepatocytes with consequent clearance of hepatitis B virus is thought to be mediated by cytotoxic [5]. Because of these mechanisms in patients with past or present infection with HBV, HIV infection can lead to significant alteration in HBV replication, antigen/antibody display and clinical consequences.…”
Section: Discussionmentioning
confidence: 99%